Modifikasi Amilosa dari Pati Tapioka dan Garut Menjadi Amilosa Asetat - Erna, Maria; Eryanti, Yum; Dahliaty, Andi (Jurnal Pilar Sains, 2008)
It has been done modification of amylose from starch tapioca and garut and then it has been changed to beamylose acetate which is degradable biopolymer. Amylose was separated from starch by method of butanolas complexing on high temperature and pressure. The yielded amylose was then acetylated by anhydrideacetate acid in glacial acetate acid solution with catalyst of concentrated sulfuric acid. Characterization wascarried out based on spectrometry of Fourier Transform Infrared Spectroscopy (FTIR). The result of amilosaspectrum showed that peak of group -OH was on 3437.25 cm and amilosa acetate spectrum had peak on1749.91 cm and it proved that acetyl reaction occurred. In this research, modification of starch tapioca wassuccessful but starch garut unsuccessful.Key words : amylose, acetate amylose.